Networks and firm location - Pontes, José Pedro (2010)
This paper models the decision of vertically-linked firms to build either partitioned or connected networks of supply of an intermediate good. In each case, the locations of upstream and downstream firms are correlated. Input specificity is relatedbothto variable costs (transport costs of the input) and fixed costs (learning costs of the use of the input). When both are low, a connected network emerges and a partitioned pattern arises in the opposite case. In the boundary region, there are multiple equilibria, either asymmetric (mixed network) or symmetric.